Level of Quality Education Services and the Effect on Students' Satisfactory: A Filed Study at Saida University - Algeria - Hamidi Zeggai; Mohammed Ouazani (University of Science and Technology, Yemen, 2017)
This study aimed to determine the effect of the quality of services offered by Saida University- Algeria- on students' satisfaction, using a scale of Service Performance (SERVPERF), which mainly focused on measuring the actual performance of the service provided to students. To achieve this objective, a questionnaire, consisting of (29) items, was developed and distributed to the study sample which consisted of 370 students.; The collected data was statistically analyzed using the (SPSS.V.20) statistical program. The study results showed that the degree of appreciation of the quality of services by students was on average, with an overall degree of 57.4%. The results also showed that students' satisfaction of the quality of educational services at the University was on average, with an overall degree of 54%. There was also a statistically significant effect on the quality of educational services to the satisfaction of students of (0.05). Finally, the study proposed a number of recommendations the most important of which were that modern methods of dealing with students should be followed, including considering their needs and voices, and taking care of them, because they are the focus of all educational processes. Keywords: Quality of service, Teaching, Students' satisfaction.